HUBUNGAN POLA MAKAN DAN STATUS GIZI DENGAN KARIES GIGI PADA ANAK DI SDN LANDUNGSARI 01 KECAMATAN DAU KABUPATEN MALANG - Wilfridus Bela Mado; Ani Sutriningsih; Dudella Desnani Firman Yasin (Nursing News : Jurnal Ilmiah Keperawatan, 2019)
Penelitian ini bertujuan mengetahui hubungan pola makan dan status gizi pada anak dengan karies gigi di SDN 01 Landungsari, Kecamatan Dau, Kabupaten Malang. Desain penelitian ini ialah korelasional untuk mengungkap hubungan antara variabel independen dengan variabel dependen, dengan pendekatan crossectional, yaitu penelitian yang hanya dilakukan dalam satu kali pengumpulan data. Populasi penelitian berjumlah 50 orang, dan sampelnya 33 orang yang diambil menggunakan teknik purposive sampling. Teknik pengumpulan data penelitian ini menggunakan kuesioner. Data hasil penelitian ini menunjukkan jumlah sampel dengan pola makan sehat sebanyak 29 orang (87,88%), status gizi baik 29 orang (87,8%) dan yang terdapat karies gigi 28 orang (84,85%). Hasil analisis data melalui uji Spearman rank correlation pada nilai signifikansi (α 0,05) dengan interprestasi jika α > 0,05 artinya H1 diterima yaitu ada hubungan antara variabel independen dengan dependen. Dengan demikian, kesimpulan penelitian ini yaitu ada hubungan pola makan dan status gizi dengan karies gigi pada anak di SDN Landungsari 01 Kecamatan Dau Kabupaten Malang. The eating pattern of elementary school students plays imporment role in the growth process since there are many nutrients in the meal. Nutrients have close relationship with dental health, the inteligenceand the body growth. If the eating pattern is not well, the body growth will be warse, besides the children’s body get thin and short. Children who don’t get good nutrition will have worse body health and can get sick easily. There is a meaning full of relationship beetwen the eating pattern and dental caries. Children who usually eat cakes will get dental caries easily. The purpose of his research is to know the correlation between eating pattern and nutrition statues with dental caries of children at SDN Landungsari 01 of Dau District of Malang Regency. The design of this research is correlative to show the corelation of the variables by using sectional cross approach. This research is implemented once for independance and dependance variable with 50 population and 33 samples which choosen by using purposive sampling technique. The data collection is using questionnaire technique. The result of the research shown that healthy eating as many as 29 children (87.88%), good nutrition status as many as 29 children (87.8%) and there are 28 children have dental caries (84.85%). The result of analysis using Spearman rank correlation test at significance value 0,05 (α 0,05) with interpretation if α > 0.05 means H1 is accepted that there is a correlation between independent variable with dependent variable. The conclusion states that there is correlation between eating patterns and nutrition status with dental caries of children at SDN Landungsari 01 of Dau District of Malang Regency. Keywords: eating pattern, nutrition status, hole teeth.